Stability Study Of Sandstone Slope Parallel To The Abu Rashada Mountain Road In Gharyan Area - NW Libya (Journal of Pure & Applied Sciences, 2022)
The evaluation and analysis of the slopes stability that are in danger of collapse is one of the things that require studies based on scientific grounds to determine the type of collapse and how it occurs and the factors affecting it, The rock masses that make up the slopes often contain cracks or joints  or rock cutouts, Thus different types of collapses are formed, plane and Wedge Failure or rotational Failure, The Importance of studying rock falls increases if their occurrence leads to human or material damages, plane Failure is one of those collapses that occur on slopes parallel to mountain roads, In this study, weak spots were observed on a sandstone slope parallel to the Abu Rashada mountain road in Gharyan Area, It also observed the occurrence of rock fall of the slope, some of which reached the road, In the initial study of the slope, it was found that there is a collapsing mass separated from the mass of the original slope. The main objective was to evaluate and study the stability of the parallel slope of the road and analyze its stability using the field and laboratory study and the use of the (RocPlane) program, The most important results were that there was a change in the water content, cohesion and friction angle values with each change in water quantities under the influence of vertical stress and shear stress applied from the direct shear device, It was found that with the increase in the amount of water from 5 mm to 25 mm 50 mm, The cohesion and the angle of friction decreased, and a decrease in the factor of safety occurred. One of the recommendations is to remove the separated part of the block that is collapsing.الحجــر الرملي